2004
DOI: 10.1007/s10800-004-3301-9
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion performance of NiAl intermetallic with Mo, Ga and Fe in neutral and alkaline media

Abstract: The corrosion resistance of mechanically alloyed NiAl intermetallics with additions of Mo, Ga and Fe, and their combinations, has been studied using potentiodynamic polarization curves and linear polarization resistance tests at room temperature. Solutions included 0.5 M NaCl and 0.5 M NaOH. The Al-42Ni+6Fe and Al-40Ni+6Fe+2Mo alloys exhibited the best corrosion resistance in NaCl whereas the highest corrosion rate was observed on Al-39Ni+6Fe+6Mo alloy, above the NiAl-base alloy. In NaOH, the highest corrosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The effect of both FeAl and NiAl intermetallic phases, in solid solution of the crystalline system B2-(Fe,Ni)Al was additive. The behavior of the NiAl phase in NaCl and NaOH (12) in the solutions with both neutral and basic pH, have shown a similar response to those observed by the Fe-Ni-Al system, with values of i corr and E corr in the order of the results obtained here (Table I). However, in acid environments the current density increases in one and two orders of magnitude in solutions of 0.5M H 2 SO 4 and 0.5M HNO 3 respectively (11).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The effect of both FeAl and NiAl intermetallic phases, in solid solution of the crystalline system B2-(Fe,Ni)Al was additive. The behavior of the NiAl phase in NaCl and NaOH (12) in the solutions with both neutral and basic pH, have shown a similar response to those observed by the Fe-Ni-Al system, with values of i corr and E corr in the order of the results obtained here (Table I). However, in acid environments the current density increases in one and two orders of magnitude in solutions of 0.5M H 2 SO 4 and 0.5M HNO 3 respectively (11).…”
Section: Resultssupporting
confidence: 81%
“…The combination of these three elements (Fe, Ni and Al) in a ternary system has also been studied because of the properties of the nickel aluminides and the modifications in the mechanical (3,4) and microstructural (5,6) properties obtained with the incorporation of the iron in the Ni-Al system. In this sense, some corrosion studies have been carried out on the behavior of the both Fe-Ni-Al (7) and Fe-Ni-Al-Cr (7,8) alloys in molten salts; and some corrosion resistance studies on both Fe-Al based and Ni-Al binary alloys at high temperature (9,10) and several corrosion assessment in aqueous solutions (11)(12)(13)(14) for the binary alloys. According to above described, in this work, the study of the corrosion of a Fe-Al-Ni base intermetallic alloy in a saline solution at room temperature was carried out by electrochemical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Most human implant materials include stainless steel AISI 316L (2,3), titanium-based alloys (4)(5)(6)(7)(8) or cobalt based alloys. The aluminides are considered carefully by its properties in aqueous corrosion such as acids, bases, chlorides and composite solutions with sulfides (9)(10)(11)(12)(13). Among the novel room temperature applications of these materials is that they can be considered their potential use such as biomaterials, or in applications in a seawater atmosphere (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The aluminides are considered carefully by its properties in aqueous corrosion such as acids, bases, chlorides and composite solutions with sulfides (9)(10)(11)(12)(13). Among the novel room temperature applications of these materials is that they can be considered their potential use such as biomaterials, or in applications in a seawater atmosphere (9)(10)(11)(12)(13). Garcia-Alonso, for instance, found that the corrosion rate of Fe 3 Altype intermetallic under three different heat treatments were within the same order of magnitude than that for 316L type stainless steel in a simulated human body fluid (9) whereas Lopez (10) obtained similar results with another iron-base alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Although several attempts to overcome this disadvantage have been carried out by adding ceramic particles [4,5] or by mechanical alloying [6], the improvement on its mechanical properties seems not to be substantial enough to employ NiAl as a structural material at room temperatures. However, its use as a coating material is justified in applications where wear [7], high temperature oxidation [8] and/or electrochemical corrosion may be present [9].…”
Section: Introductionmentioning
confidence: 99%